COVID-19: Sleep, Circadian Rhythms and Immunity – Repurposing Drugs and Chronotherapeutics for SARS-CoV-2 - Giri, Allan; Srinivasan, Ashokkumar; Sundar, Isaac Kirubakaran (Frontiers in Neuroscience, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has affected nearly 28 million people in the US and has caused more than five hundred thousand deaths as of February 21, 2021. As the novel coronavirus continues to take its toll in the US and all across the globe, particularly among the elderly (>65 years), clinicians and translational researchers are taking a closer look at the nexus of sleep, circadian rhythms and immunity that may contribute toward severe COVID-19 disease. SARS-CoV-2-induced multi-organ failure affects both central and peripheral organs, causing increased mortality in the elderly. However, whether differences in sleep, circadian rhythms, and immunity between older and younger individuals contribute to the age-related differences in systemic dysregulation of target organs observed in SARS-CoV-2 infection is still being investigated. Current literature demonstrates the emerging role of sleep, circadian rhythms, and immunity in the development of chronic pulmonary diseases and respiratory infections in human and mouse models. The exact mechanism underlying acute respiratory distress syndrome (ARDS) and other cardiopulmonary complications in elderly patients in combination with associated comorbidities remain unclear. Nevertheless, understanding the nexus of sleep, circadian clock dysfunction in target organs, and immune status of patients with SARS-CoV-2 may provide novel insights into possible therapies. Chronotherapy is an emerging concept that is gaining attention in sleep medicine. Accumulating evidence suggests that nearly half of all physiological functions follow a strict daily rhythm. However, healthcare professionals rarely take implementing timed administration of drugs into consideration. In this review, we summarize recent findings directly relating to the contributing roles of sleep, circadian rhythms and immune response in modulating infectious disease processes, and integrate chronotherapy in the discussion of the potential drugs that can be repurposed to improve the treatment and management of the coronavirus disease -19 (COVID-19).